2022
DOI: 10.4081/ejtm.2022.10460
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm impairment in patients admitted for severe COVID-19

Abstract: Among patients affected by the virus COVID-19, physicians have observed ventilation disorders. It is relevant to assess neurological involvement, including the role of diaphragmatic function. Its possible impairment could be related to the systemic inflammatory response and disease progression that both typify COVID-19 infection. We distinguished two groups (severe group (SG) and mild group (MG)) according to the severity of respiratory symptomatology. We performed neurophysiological and sonography studies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…39 Parlak et al 21 found the cut-off value of diaphragm thickness as 3.67 mm for ICU admission and 3.47 mm for mortality. Many studies conducted with US also indicated that DD was lower in the severe patient group, 40 while the diaphragm was thinner in patients that developed complications, 9 and mechanical ventilation and mortality could be predicted by a diaphragm examination performed within 12 h of hospitalization. 41 Our results are in agreement with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…39 Parlak et al 21 found the cut-off value of diaphragm thickness as 3.67 mm for ICU admission and 3.47 mm for mortality. Many studies conducted with US also indicated that DD was lower in the severe patient group, 40 while the diaphragm was thinner in patients that developed complications, 9 and mechanical ventilation and mortality could be predicted by a diaphragm examination performed within 12 h of hospitalization. 41 Our results are in agreement with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…According to observations, body tissues infected with SARS-CoV-2 have increased angiotensin-converting enzyme 2 (ACE-2) expression; hence, the ACE-2 receptors may play an essential role in promoting viral particle invasion into neurons and other body structures, such as the diaphragm muscle, causing breathing impairment [ 10 , 11 ]. Notably, researchers reported that epimysial and perimysial fibrosis was more than twofold more significant in the diaphragm muscles of COVID-19-infected ICU patients compared to control ICU patients in a study on the diaphragm musculature in COVID-19-infected ICU patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be corroborated by the observed reduced VO 2 p values in many of them, and by the fact that this parameter can get better with physical training [ 39 , 40 , 41 ]. A possible alternative might lie in an altered central control of ventilation [ 42 , 43 , 44 , 45 ] or in an underlying vascular dysfunction, described in post-MIS-C children [ 23 ].…”
Section: Discussionmentioning
confidence: 99%